Dynamic model for using casterboard by a humanoid robot. (18th May 2020) - Fukai, R.; Yagi, K.; Mori, Y.
ABSTRACT: The efficacy of traveling and movement is substantially enhanced by the use of wheel mechanisms, particularly when compared to bipedal locomotion. Humanoid locomotion can also be extended using appropriate tools. In this study, we focus on the casterboard as a tool that facilitates traveling, because it has comparatively high portability, and the rider can move forward without pushing off the ground. We present a dynamic model for the use of the casterboard in a humanoid robot. Given that the ankles and waist of the rider play a key role in traveling using the casterboard, the angles of those joints are utilized as the input of the proposed model. A simplified small-scale robot is used to determine essential elements, and a modified casterboard is employed to eliminate the risk of falling without loss of its unique properties, for verification of the dynamic model. Using simulations and experiments, it is demonstrated that the dynamic model effectively emulates the behavior of the actual setup with respect to forward movement and turning. The model serves as the basis for the planning of a reference trajectory using the casterboard. GRAPHICAL ABSTRACT: